A O04 Identifying Predictive Factors for Prolonged use of Nutritional Support After Oesophagogastric Cancer Resections. (7th December 2022) - Chana, Prem; Moore, Jonathan; Estevez-Cores, Javier; Renna, Maxwell; Jagielka, Karolina; Waller-Alvarez, Carmen; Baker, Cara; Kelly, Mark; Davies, Andrew; Gossage, James
Abstract: Background: In the era of evidence-based practice, there remains significant variation in peri-operative nutritional strategies for patients undergoing oesophagogastric (OG) cancer resections. Although dietary support is accepted as essential for this patient group, the use of feeding adjuncts, such as parenteral nutrition (PN) or enteral feeding tubes, varies widely. In addition, the clinical benefit of peri-operative supplementary feeding remains uncertain, especially since the evolution to minimally invasive OG surgery, introduction of ERAS and drive for early oral intake. Despite improvements in peri-operative nutrition pathways, risks associated with feeding adjuncts remain. There are also increased financial costs associated with peri-operative nutritional support which require consideration. After analysing unit peri-operative outcomes, it was hypothesised that routine feeding adjunct use may be unnecessary for most patients who meet oral nutritional goals early and should instead be reserved for patients with an increased risk of supplementary post-operative nutritional requirement.The primary aim of this study was to evaluate which clinicopathological factors were associated with prolonged use of PN after OG surgery. The secondary aim was to evaluate the associated morbidity and healthcare costs of PN use. Methods: A retrospective cohort study of 518 patients undergoing oesophagectomy or total gastrectomy for cancer at Guy's and St Thomas' NHS Foundation Trust, London, UK, between 2015 and 2021. The standard feeding regimen after oeosphagectomy or total gastrectomy at St Thomas' involves PN for a median of eight days post-operatively. Oral intake is initiated after a contrast swallow is performed on day three for uncomplicated patients. The primary outcome was prolonged use of post-operative PN, defined as nine-days or more PN during the index admission. Clinicopathological characteristics were compared using the Chi square test. The relationship between these characteristics and PN use was evaluated using logistic regression analysis, providing odds ratios (OR) with 95% confidence intervals (CI) adjusting for age, sex, BMI, comorbidities, histology, anastomosis location, surgical access, pre-operative weight loss, pre-operative supplementary feeding. The prognostic ability of clinicopathological characteristics to predict prolonged PN use were compared using receiver operator characteristic (ROC) analysis to calculate area under the curve (AUC). An economic model was developed using described PN related complication rates from the published literature and 2021 NHS tariffs. Results: Predictive factors for prolonged PN use on adjusted analysis included age over 65 (HR 1.70 95% CI 1.14–2.52), pre-operative weight loss (0–10%: HR 1.67 95% CI 1.09–2.56, >10%: HR 2.21 95% CI 1.05–4.66), open surgery (HR 1.64 95% CI 1.03–2.62) and an OG anastomosis located in the neck (HR 2.50 95% CI 1.35–4.65). Patients with a BMI over 25 had a lower chance of prolonged PN use (HR 0.65 95% CI 0.43–0.98). Other characteristics were not prognostic. ROC curve analysis demonstrated that anastomosis location (AUC 0.59), age (AUC 0.57) and surgical access (AUC 0.56) were the most prognostic factors. The combination of parameters included in the adjusted model provided an AUC of 0.67. Potential PN and line related complications included: deranged liver biochemistry (18.0%), deranged blood sugars (9%), line infection (1.4%) and line thrombus (0.8%). An eight-day course of PN was calculated to cost £884 with average treatment related complication costs of £176 per patient. Using the mean number of patients treated per year over the past three years (N = 112) the projected service savings were £75, 912 per year if PN was reserved for patients with high-risk characteristics. Conclusions: This study has demonstrated that several patient and treatment related factors are associated with an increased risk of needing prolonged adjunctive nutritional support after OG surgery. As surgical practice has evolved to minimally invasive surgery and ERAS with subsequently low peri-operative complication rates, the clinical benefits of short course adjuvant feeding may not be seen in patients who progress promptly to appropriate oral intake. Therefore, we propose the introduction of a tailored treatment pathway, based on pre-operative characteristics which excludes the routine use of post-operative feeding for low-risk patients. The study also demonstrates that a change in practice can lead to considerable cost savings. The model demonstrated in this study can be applied to all feeding adjuncts and can therefore be universally adopted in any UK/global unit regardless of supplementary feeding route preference. It will encourage high-performance by promoting a patient-centred and individualised approach to peri-operative nutrition which is currently lacking in many aspects of our clinical practice. Further work in the form of a randomised trial may be explored to better understand the need and benefit of supplementary feeding methods after OG resection as the specialty continues to evolve.